Học từ vựng và thành ngữ tiếng Anh trình độ nâng cao = Advanced vocabulary and idioms - Thomas, B. J. (Nxb Tp.HCM, 1997)
This book is for students who already have a good command of the basic structures of English and who now wish to increase their range of vocabulary and idioms, and to gain more knowledge of particular styles of English.